Analysis of the complement sensitivity of oral treponemes and the potential influence of FH binding, FH cleavage and dentilisin activity on the pathogenesis of periodontal disease. (3rd June 2014) - Miller, D.P.; McDowell, J.V.; Bell, J.K.; Goetting‐Minesky, M.P.; Fenno, J.C.; Marconi, R.T.
Summary Treponema denticola, a periopathogen, evades complement‐mediated killing by binding the negative complement regulatory protein factor H (FH) to its surface via the FhbB protein. Paradoxically, bound FH is cleaved by T. denticola's dentilisin protease, a process hypothesized to trigger localized dysregulation of complement activation in periodontal pockets. The ability of other oral treponemes to evade complement‐mediated killing and bind and cleave FH has not been assessed. In this report, we demonstrate that representative isolates of Treponema socranskii, Treponema medium, Treponema pectinovorum and Treponema maltophilum are also serum resistant, whereas Treponema vincentii and Treponema amylovorum are serum sensitive. Although T. denticola's ability to evade complement‐mediated killing is strictly dependent on FH binding, other serum‐resistant treponemal species lack FhbB and do not bind FH, indicating an FH‐independent mechanism of complement evasion. To assess the influence of FhbB sequence variation on FH binding and cleavage by T. denticola, fhbB sequences were determined for 30 isolates. Three distinct phyletic types were identified. All T. denticola strains bound FH and were serum resistant, but differences in binding kinetics, dentilisin activity and FH cleavage ability were observed. Based on these analyses, we hypothesize that the composition of the T. denticola population is a determining factor that influences the progression and severity of periodontal disease.